Application Of Liquid Organic Fertilizer (Poc) To The Growth And Yield Of Organically Cultivated Glycine max (L.) Soybeans - Reski Bengkal; Jeanne M. Paulus; Paula C. H. Supit; Sesilia A. Wanget; Meity R. Rantung; Yefta Pamandungan (Sam Ratulangi University, 2023)
This study aims to examine the effect of liquid organic fertilizer (POC) on the growth and yield of organically cultivated soybeans and to obtain the best concentration to increase the growth and yield of organically cultivated soybeans. This research was conducted in Sendangan Village, Sonder District, Minahasa Regency. The research design used a randomized block design (RBD) consisting of 5 treatments and 4 replications so that there were 20 plots, namely 0 ml/liter of water (P0), 50 ml/liter of water (P1), 100 ml/liter of water (P2) treatment. , 150 ml/liter of water (P3), 200 ml/liter of water (P4). Variables observed: plant height, number of branches, number of pods, number of root nodules, and production per plot. The results showed that POC had an effect on the number of branches aged 34 and 44 days after planting, the number of root nodules and production per plot. The best POC concentration is achieved at 200 ml/liter of water with the highest value of 225.40 g or the equivalent of 2.25 tonnes.ha -1 Keywords : Soya bean, Liquid Organic Fertilizer,Â Concentration. Abstrak Penelitian ini bertujuan untuk mengkaji pengaruh pupuk organik cair (POC) terhadap pertumbuhan dan hasil kedelai yang dibudidayakan secara organik dan mendapatkan konsentrasi terbaik untuk meningkatkan pertumbuhan dan hasil kedelai yang dibudidayakan secara organik. Penelitian ini dilaksanakan di Desa Sendangan, Kecamatan Sonder, Kabupaten Minahasa. Rancangan penelitian ini menggunakan rancangan acak kelompok (RAK) yang terdiri dari 5 perlakuan dan 4 ulangan sehingga berjumlah 20 petak yaitu perlakuan 0 ml/liter air (P0), 50 ml/liter air (P1), 100 ml/liter air (P2), 150 ml/liter air (P3), 200 ml/liter air (P4). Variabel yang diamati : tinggi tanaman, jumlah cabang, jumlah polong, jumlah bintil akar, dan produksi per petak. Hasil penelitian menunjukan bahwa POC berpengaruh terhadap jumlah cabang umur 34 hst, 44 hst, jumlah bintil akar dan produksi per petak. Konsentrasi POC terbaik dicapai pada 200 ml/liter air dengan nilai tertinggi tertinggi yaitu 225,40 g atau setara dengan 2,25 ton.ha -1 Kata kunci : Kedelai, Pupuk Organik Cair, konsentrasi.